Pancreatic Ductal Adenocarcinoma and Immune Checkpoint Inhibitors: The Gray Curtain of Immunotherapy and Spikes of Lights - Rita Balsano; Valentina Zanuso; Angelo Pirozzi; Lorenza Rimassa; Silvia Bozzarelli (Current Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is a dismal disease with a poor 5-year overall survival rate (~10%). The revolution of immunotherapy in clinical oncology has not substantially changed clinical outcome for patients with PDAC. Despite outstanding efforts, neither immune checkpoint inhibitors (ICIs) alone, nor in combination with chemotherapy or targeted therapies have shown encouraging results. This failure mirrors the lack of knowledge about the real key players of immune system senescence and the complexity of the tumor microenvironment in PDAC. However, some hope can be derived from PARP-inhibitor combinations, vaccines, and CAR-T-cells therapy. In this review, we comprehensively summarize the latest updates about the use of ICIs in PDAC, focusing on clinical evidence and ongoing studies highlighting explanations for the failure of immunotherapy and possible solutions.